Student nurses' opinions regarding the clinical learning environment and supervision at Malamulo Hospital, Malawi - Kachiwala, Annie Yanjanani (My University, 2007)
The learning environment and supervision in clinical placement play an important role in nursing education. The purpose of this study was to describe the opinions of student nurses with regard to the clinical learning environment and supervision at Malamulo Hospital, Malawi. A quantitative descriptive design was used. Data were collected from nursing students at Malamulo College of Health Science using the Clinical Learning Environment Scale (CLES) comprising structured questions. The questionnaire was administered to the total population of students (N=84) and the response rate was 87% (n=73). Descriptive statistics were used to analyze data. Relationships between variables were determined by using Fisher’s exact test and the t-test. The findings revealed that the majority of the participants were satisfied with their clinical learning environment and supervision in their latest clinical placement. Particularly, they were satisfied with the relationship that prevailed between students and members of nursing staff, feedback they received from their supervisors, the nursing care given to patients and the quality of learning opportunities. However, it was determined that nurse teachers did not regularly supervise students and also that some students were not clear about the nursing philosophy of their wards. Ward familiarization processes were not well planned as indicated by about a third of the participants. More than one third also indicated that the learning situations were not sufficient and not meaningful. While 73.98 % indicated that they received constructive feedback from their supervisors, about half of the participants indicated that the feedback was not given continuously.The majority (67.76%) of the participants experienced team supervision as opposed to individual supervision. Therefore it is recommended that nurse teachers increase the number of visits to the wards when students are in clinical placement to improve quality of clinical learning. The nursing college may need to have specific clinical instructors who are trained in clinical supervision and who will be available for students in the clinical placements regularly. The ward managers and the nursing staff need to clarify and display their ward nursing philosophy so that both nurses and students can have a common understanding and common goal in the provision of nursing care. It is also recommended that feedback be given to students continuously to enhance learning.
Student Number : 0317159E - MSc(Nursing) research report - School of Therapeutics - Faculty of Health Sciences
Keywords: Student nurse; Clinical learning environment; Clinical supervision; Clincal supervisor